Missing mate pairs reported as poly-G reads can confound analyses of rare members of microbial assemblages - Amrit K. Dhillon; Aspen Workman; Larry A. Kuehn; Bernadette Earley; Sara Louise Cosby; Amy J. Powell; Tara G. McDaneld; Gavin C. Conant (Ecological Genetics and Genomics, 2025)

Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núnez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Corrigendum to “long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum” [science of the total environment, 908 (2024)/ 168,042] - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Interdisciplinary challenges for wildfire futures - T.A. Fairman; J. Aryal; P.J. Baker; A. Best; J. Cawson; H. Clarke; M.S. Fletcher; L. Gibbs; G. Foliente; L. Godden; M. Gibson; L. Kelly; et al. (Environmental Science & Policy, 2025)

Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

A dynamic in vitro developing testis model reflects structures and functions of testicular development in vivo - Susanna Wegner; Tomomi Workman; Julie Juyoung Park; Sean Harris; James Wallace; Ian Stanaway; Sungwoo Hong; Brad Hansen; William C. Griffith; Elaine M. Faustman (Reproductive Toxicology, 2023)

Alteration of oral microbiome composition in children living with pesticide-exposed farm workers - Ian B. Stanaway; James C. Wallace; Sungwoo Hong; Carly S. Wilder; Foad H. Green; Jesse Tsai; Misty Knight; Tomomi Workman; Eric M. Vigoren; Marissa N. Smith; William C. Griffith; Beti Thompson; et al. (International Journal of Hygiene and Environmental Health, 2023)

Adrenoceptor sub-type involvement in Ca2+ current stimulation by noradrenaline in human and rabbit atrial myocytes - Priyanka Saxena; Rachel C. Myles; Godfrey L. Smith; Antony J. Workman (Pflügers Archiv - European Journal of Physiology, 2022)
Atrial fibrillation (AF) from elevated adrenergic activity may involve increased atrial L-type Ca 2+ current (I CaL ) by noradrenaline (NA). However, the contribution of the adrenoceptor (AR) sub-types to such I CaL -increase is poorly understood, particularly in human. We therefore investigated effects of various broad-action and sub-type-specific α- and β-AR antagonists on NA-stimulated atrial I CaL . I CaL was recorded by whole-cell-patch clamp at 37 °C in myocytes isolated enzymatically from atrial tissues from consenting patients undergoing elective cardiac surgery and from rabbits. NA markedly increased human atrial I CaL , maximally by ~ 2.5-fold, with EC 75 310 nM. Propranolol (β 1 + β 2 -AR antagonist, 0.2 microM) substantially decreased NA (310 nM)-stimulated I CaL , in human and rabbit. Phentolamine (α 1 + α 2 -AR antagonist, 1 microM) also decreased NA-stimulated I CaL . CGP20712A (β 1 -AR antagonist, 0.3 microM) and prazosin (α 1 -AR antagonist, 0.5 microM) each decreased NA-stimulated I CaL in both species. ICI118551 (β 2 -AR antagonist, 0.1 microM), in the presence of NA + CGP20712A, had no significant effect on I CaL in human atrial myocytes, but increased it in rabbit. Yohimbine (α 2 -AR antagonist, 10 microM), with NA + prazosin, had no significant effect on human or rabbit I CaL . Stimulation of atrial I CaL by NA is mediated, based on AR sub-type antagonist responses, mainly by activating β 1 - and α 1 -ARs in both human and rabbit, with a β 2 -inhibitory contribution evident in rabbit, and negligible α 2 involvement in either species. This improved understanding of AR sub-type contributions to noradrenergic activation of atrial I CaL could help inform future potential optimisation of pharmacological AR-antagonism strategies for inhibiting adrenergic AF.

Cerebellar Contributions to Motor Impairments in People with Multiple Sclerosis - Alexandra C. Fietsam; Warren G. Darling; Jacob J. Sosnoff; Craig D. Workman; John Kamholz; Thorsten Rudroff (The Cerebellum, 2021)

Shade affects magnitude and tactics of juvenile Chinook salmon antipredator behavior in the migration corridor - Megan C. Sabal; Michelle L. Workman; Joseph E. Merz; Eric P. Palkovacs (Oecologia, 2021)
Environmental conditions strongly affect antipredator behaviors; however, it is less known how migrating prey adjust antipredator behavior in migration corridors, in part, because active migrants are difficult to observe and study. Migrants are vulnerable and encounter many predators in the corridor, and their propensity to travel towards their destination ties antipredator behavior with movement. We evaluated how environmental risk cues in the migration corridor including in-water habitat structure (present, absent) and overhead shade (sun, shade), and salmon origin (hatchery, wild) affected how juvenile Chinook salmon ( Oncorhynchus tshawytscha ) reacted to a live predator. We measured how salmon react to predation risk as the difference in time to swim downstream through a 9.1-m long field enclosure with or without a live predatory largemouth bass ( Micropterus salmoides ). Shade significantly modified the reaction to the predator, and it did so in two ways. First, the magnitude of antipredator behavior was larger in shade compared to direct sun, which suggests salmon perceived shade to be a riskier environment than sun. Second, the escape tactic also varied; salmon slowed down to be cautious in shade and sped up in sun. Structure did not significantly affect behavior and hatchery and wild salmon behaved similarly. Our study suggests that environmental risk cues can shape the magnitude and tactics of how migrants react to predation risk and illustrates how these responses relate to movement with potential to scale up and affect migration patterns.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Erratum to: Remodelling of human atrial K+ currents but not ion channel expression by chronic β-blockade - Gillian E. Marshall; Julie A. Russell; James O. Tellez; Pardeep S. Jhund; Susan Currie; John Dempster; Mark R. Boyett; Kathleen A. Kane; Andrew C. Rankin; Antony J. Workman (Pflügers Archiv - European Journal of Physiology, 2014)

Remodelling of human atrial K+ currents but not ion channel expression by chronic β-blockade - Gillian E. Marshall; Julie A. Russell; James O. Tellez; Pardeep S. Jhund; Susan Currie; John Dempster; Mark R. Boyett; Kathleen A. Kane; Andrew C. Rankin; Antony J. Workman (Pflügers Archiv - European Journal of Physiology, 2012)

Bacteriocin-like inhibitory substances from Campylobacter spp. - Suzanne Nicole Workman; Floyd E. Been; Simera R. Crawford; Marc C. Lavoie (Antonie van Leeuwenhoek, 2008)

Pediatric cancer knowledge: Assessment of knowledge of warning signs and symptoms for pediatric cancer among Brazilian community health workers - Gloria M. Workman; Raul C. Ribeiro; Shesh N. Rai; Arli Pedrosa; Don E. Workman; Francisco Pedrosa (Journal of Cancer Education, 2007)

DNA microarray analysis of fim mutations in Escherichia coli - M. Schembri; D. Ussery; C. Workman; H. Hasman; P. Klemm (Molecular Genetics and Genomics, 2002)

Biphasic Material Properties of Lytic Bone Metastases - Cari M. Whyne; Serena S. Hu; Kimberly L. Workman; Jeffrey C. Lotz (Annals of Biomedical Engineering, 2000)

The effect of storage environment on the infection of potato tubers byAlternaria solani - E. C. Nnodu; M. D. Harrison; M. Workman (American Journal of Potato Research, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Effects of soil fumigation with Telone C on soil and plant nitrogen, verticillium wilt and yield of Norland and Norgold potatoes - M. Workman; M. D. Harrison; C. H. Livingstone (American Journal of Potato Research, 1977)